Nutrient accumulation in the shoots of physic nut grown in two edaphoclimatic conditions - Sávio Coelho Magalhães; Enilson de Barros Silva; Evander Alves Ferreira; Thassio de Menezes Reis; Gustavo Antônio Mendes Pereira; Filipe Vieira Araújo; Tânia Pires da Silva (Semina: Ciências Agrárias, 2018)
The possibility of using physic nut oil as an alternative energy source indicates that it is necessary to carry out studies concerning the absorption and accumulation of nutrients in the distinct phases of development of the crop for the appropriate management of fertilizer application. Given this information, this study aimed to evaluate the accumulation of nutrients in the shoots of physic nut plants, as well as to identify critical nutrient uptake by this crop. The experiments were set up independently in two different locations, from May 2010 to March 2013, and using the same procedures. The locations were characterized as follows: dystrophic Red Latosol in the municipality of Curvelo, MG; typical Quartzarenic Neosol in the municipality of Diamantina, MG. The experiments were conducted in a randomized block design with three replicates, the treatments being the evaluation times of the physic nut plants in both experiments. The collection times were every 30 days from planting of the seedlings in the field for a period of 1036 days, corresponding to 36 evaluations. After collection, the samples were prepared and submitted to chemical analysis of the nutrient content of the plant material. The contents were reported as nutrient content of the leaves, stems and fruit of physic nut plants. According to the results, it can be concluded that nutrient accumulation was higher in the edaphoclimatic conditions of Curvelo compared to the conditions of Diamantina. The concentration of macronutrients was in the following order: K > Ca > N > P > S > Mg in Diamantina and N > Ca > K > P > Mg > S in Curvelo. Accumulation of micronutrients in the shoots at 1036 days after planting physic nut seedlings in the field was in the following order: Mn > B > Fe > Zn > Cu in Diamantina and Mn > Fe > B > Zn > Cu in Curvelo.